Aspectos da formação humana: paidéia, bildung e geofilosofia da educação - Fernanda Antônia Barbosa da Mota; Heraldo Aparecido Silva (EccoS – Revista Científica)
The purpose of this article is to present a possible course for the study of human formation within the philosophy of education and also to offer a preamble about our version of the philosophy of Deleuzian education. The study is based on theoretical references such as Jaeger (1995), Chauí (2002), Paviani (2003), Pagni and Silva (2007), Gallo (2007; 2008), Deleuze and Guattari (2010), among others. Initially, we favor the relations between Philosophy and Education in antiquity (Paidea) and modernity (Bildung), emphasizing the most influential philosophical ideas for education. In contemporaneity, we highlight some of the most expressive theoretical contributions constituent of the Brazilian educational philosophical scenario: Dewey, Adorno and Deleuze. Finally, the article shows that Geophilosophy of Education connects rhizomatically the philosophical and educational territories without incurring the linear reproduction of the history of philosophy or education, but looking for platforms for the creation of new concepts.